INVERSE NODAL PROBLEM FORp LAPLACIAN DIFFUSION EQUATION WITH POLYNOMIALLY DEPENDENT SPECTRAL PARAMETER - Gülşen, Tüba; Yılmaz, Emrah (My University, 2016)
In this study, solution of inverse nodal problem for one-dimensionalp-Laplacian diğusion equation is extended to the case that boundary condition depends on polynomial eigenparameter. To ...nd the spectral datas aseigenvalues and nodal parameters of this problem, we used a modi...ed Prüfersubstitution. Then, reconstruction formula of the potential function is alsogiven by using nodal lenghts. Furthermore, this method is similar to used in[1], our results are more general.
Keywords: Matematik